Variables of the Family, School, and Social Environment Context That Determine Bullying in Adolescents in Medellín, Colombia, 2014 (2017)
ABSTRACT : This study determines the prevalence of bullying and the variables that explain the phenomenon in adolescents from educational institutions in Medellín. A survey involving school climate, family functionality, and bullying was applied in a representative sample of 3,460 adolescents. The information was analyzed with descriptive measures, Z-test, prevalence ratios, Mann-Whitney test, and logistic regression. The overall prevalence of bullying was 18.3%, being higher among those who report family dysfunction, delinquent behavior at school, bad relationships with teachers, and insecurity in the neighborhood. The bullying is a complex phenomenon that involves the social framework, relationships within the family and the teachers.